H∞ voltage control of a direct high-frequency converter - William G. Garlick; Argyrios C. Zolotas (2009)
Providing a secure power network is a demanding task but as network complexity is expected to grow with the connection of large amounts of distributed generation so the problem of integration, not just connection, of each additional generator becomes more protracted. A fundamental change to contemporary network architectures may eventually become necessary and this will provide new opportunities for power electronic converters to deliver advanced management and new power flow control features. Direct resonant converters (Dang 2005), could be used in novel devices such as the Active Transformers (Garlick 2008). The key to the successful exploitation of these devices will be their versatility, controllability and cost efficiency.